Response Surface Method Application in Tofu Production Liquid Waste Treatment - Hefni Effendi; Romi Seroja; Sigid Hariyadi (Universitas Gadjah Mada, 2019)
Liquid waste of tofu production has a high content of organic matter which can lead to a decrease in water quality. This study was aimed to obtain an optimal combination of duration and waste concentration in tofu liquid waste treatment using Chrysopogon zizanioides. Response surface method using Design Expert 7.0 software was applied to optimize combination response of duration (3, 9, 15 days) and waste concentration (20, 40, 60%), aided by Design Expert 7.0 software. The optimum treatment was 15 days with 20% waste concentration, reducing 55.48% of COD, 37.86% BOD, 93.51% TSS, 87.86% Turbidity, increasing DO to 7.2 mg/L and pH to 7.2.